Partisipasi Masyarakat dalam Mewujudkan Program Pojok Baca Digital (POCADI) di Kota Tebing Tinggi - Shandya, Jihan; Ridwan, Mohammad (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
The decreasing interest in reading books has resulted in books being replaced by digital media. Changes in community behavior in the era of disruption occur because people are more interested in information obtained through online news that is spread on various websites and social media. This study aims to determine community participation in the implementation of the Digital Reading Corner (POCADI) program in Tebing Tinggi City which focuses on community involvement in utilizing the Pocadi program to increase reading interest and digital literacy in Tebing Tinggi City. This research uses descriptive qualitative research methods. Data collection techniques are interviews, observation and documentation. The results obtained using the analysis of the theory of community participation proposed by Cohen and Uphoff show that the Pocadi program still has not shown a positive impact in increasing interest in reading and literacy in the community. Community participation in the Pocadi program has not been carried out optimally at each stage. Especially at the implementation stage, where the community has not fully utilized Pocadi as a reading place that supports an increase in interest in reading and digital literacy in the community.